Simpler estimators for K-Flated Poisson distribution - Razik Ridzuan Mohd Tajuddin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The point of inflation or deflation for Poisson distribution cannot be defined objectively. Therefore, the maximum likelihood function may not be used efficiently to derive an estimator. In this paper, two simpler estimators for k-flated Poisson distribution, named as ratio of frequency (RFE) and probability estimators (PE) were developed and discussed. The estimators are based on the position of ‘flation’,